Data Visualization and Mental Models in the Understanding and Use of Complex Systems - B. Charles Tatum (Research Developments in Science and Technology Vol. 8, 2022)
We have come to rely on visual objects to understand and use complex data patterns. We have also adopted metaphors (mental models) for manipulating information. This chapter has two parts. Part one deals with data visualization (the use of visual objects to help understand and use complex sets of data). I first provide a brief history of data visualization. I then review some contemporary trends. Finally, I report on a recent study that compares a visual presentation of data (a bar chart) to a more traditional textual presentation (a spreadsheet) and show that the visual rendition is superior in several ways. Part two of the chapter discusses the notion of mental models (metaphors held in the mind). I discuss the theory that underlies mental models and provide many examples of these models. I then present a study that uses a mental model (a water tank system) to symbolize a Navy manpower planning process. The study reveals that the water tank metaphor is a realistic model, but falls short of increasing the participants’ understanding or use of the planning process. The research suggests that some models should employ features of animation. In general, it is concluded that evidence-based visualizations and mental models are useful aids to understanding data presentation and use.